PROFIL PENYIMPANAN OBAT DI INSTALASI FARMASI RUMAH SAKIT SCHOLOO KEYEN KABUPATEN SORONG SELATAN PAPUA BARAT - sukmawati sukmawati; Rizqi Nur Azizah; Muhammad Irman (As-Syifaa Jurnal Farmasi, 2022)
The drug storage stage is part of the management of pharmaceutical preparations. Storage of drugs is good and correct can maintain the quality of a drug and facilitate the search and control and can reduce the risk of loss. This study aims to examine the profile of drug storage in the Pharmacy Installation of the Keyen Scholoo Hospital, South Sorong, West Papua. This study has used a descriptive method by means of direct interviews and observations with a check list related to drug storage. The parameters are based on Peraturan Menteri Kesehatan No 72 tahun 2016 dan Kementerian Kesehatan tahun 2019  regarding technical guidelines for pharmaceutical service standards in hospitals using percentage analysis. The results of the study concluded that the storage of drugs at the Pharmacy Installation of Scholoo Keyen Hospital based on the storage location was in the poor category with a conformity percentage of 61%. Meanwhile, based on the storage method, it is in the good category with a conformity percentage of 75% and based on the storage system/principle it is in the good category with a 100% conformity percentage.